Controle tolerante com reconfiguração estrutural acoplado a sistema de diagnóstico de falhas - Reis, Lucas Lacerda Gomes (2008)
The requirement of increasing the availability of plants is present in the current industrial park. The availability represents the satisfactory operation of a plant even during process failures. A system with these characteristics is defened as a system fault-tolerant. For the implementation of a fault-tolerant system is important to use automatic monitoring techniques capable of providing accurate information on the state of the process and form the basis for the recovery of the diagnosed condition. This structure functions as the main source of information for supervisory systems responsible for corrective actions to accommodate efects caused by failures. In this work, techniques for fault detection and diagnosis based on data from the plant operation and mathematical models of processes are used to monitor the state of industrial processes. The tolerant control techniques proposed in this work is based on the union of dierent strategies for process monitoring, a process and control reconfiguration and control goals adaptation to obtain new control structures. Thus, the proposed system will add features for fault tolerance by coupling fault detection and diagnosis with the structural reconfiguration of the control system. In this context, this work presents a novel fault-tolerant control scheme illustrating their successful application through case studies on PID control, optimal control and predictive control structures.